ANALISIS HUBUNGAN ANTARA PENGETAHUAN DENGAN APLIKASI TANGGAP DARURAT KEBAKARAN PADA PERAWAT DI INSTALASI RAWAT INAP RSUD PASAR REBO, JAKARTA TIMUR - Delvi Nur Oktaviani; Ida Wahyuni; Baju Widjasena (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
The risk of fire in hospital had the highest rating compared to another places, because in every single task was done by using electrical energy as a primary energy source. The existence of a fire management system in hospital was not enough to overcame the fire without knowledge and the ability of fire emergency response that might be possessed of all workers. The general purpose of this research to analyzed the correlation between knowledge and application of fire emergency response on nurses in patient care installation of general hospital of Pasar Rebo, East Jakarta. The specific purpose of this research to analyzed the correlation between the characteristics of participant and application of fire emergency response. The characteristics of participant included fire safety education, fire safety training, fire experience, age, and working experience. This research was an analytic quantitative research by cross sectional approach. The participants of this research were 65 nurses. By using the correlation test, the results showed that there was not a significant correlation between participant’s characteristics (fire safety education, fire safety training, fire experience, age, and working experience) and application of fire emergency response (p >0,05). And also there was not a significant correlation between knowledge and application of fire emergency response (p >0,05). The general hospital of Pasar Rebo was expected to held the fire safety education and fire safety training regularly, at least once a year.